Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A scenario-based risk assessment framework for tyre wear particles in European seas - T. Maes; R. Ruhl; L. Sørensen; G. Fylakis; B.H. Hansen; R. Nepstad; A. Igartua; T. Vlachogianni; A.M. Booth (Journal of Hazardous Materials, 2026)

Multi-colored traps can enhance monitoring programs for native and non-native longhorn beetles in forest ecosystems - Laura Besana; Giacomo Santoiemma; Antonio Biondi; Everett G. Booth; Giacomo Cavaletto; Valerio Caruso; Sarah M. Devine; Joseph A. Francese; Emily Franzen; Antonio Gugliuzzo; Jerzy M. Gutowski; Robert Johns; et al. (Forest Ecology and Management, 2026)

Improving conservation outcomes for seadragons: data, knowledge gaps, and future directions - Chrissy A. Tustison; Nerida G. Wilson; Greg W. Rouse; David J. Booth; Maarten De Brauwer (Reviews in Fish Biology and Fisheries, 2025)
Seadragons are charismatic fishes endemic to Australia’s Great Southern Reef and are flagships for marine biodiversity. Due to their unique appearances and behaviors, seadragons are of interest for both scientific research and broader conservation purposes. However, studies on wild seadragon populations are challenging to implement, and peer-reviewed data on population demographics, life histories, and other aspects of seadragon biology and ecology are currently limited. Seadragon habitats, including kelp-covered reefs and seagrass meadows, have declined in various areas of the southern Australian coast, spurring concerns that seadragon abundances may also be contracting. The lack of range-wide baseline data on seadragon populations has precluded a robust understanding of their vulnerability to extinction, and further conservation-focused research has been recommended by past studies. Here, we summarize existing research on the three known seadragon species: common, leafy, and ruby seadragons, with the aim of improving future conservation outcomes for seadragons. Range-wide population size estimates and trends in abundance data are key knowledge gaps preventing accurate extinction risk assessments. Lack of data about basic ecological and biological factors such as longevity and reproduction further hinder effective conservation actions. We describe developing research methodologies including citizen science, machine learning, habitat mapping, and molecular methods that show promise for improving outcomes for these iconic fishes and the habitats they rely on.

Efficacy of unbaited and baited green multi-funnel traps for detection of Agrilus species and other wood-boring beetle taxa - Giacomo Santoiemma; Jon Sweeney; Everett G. Booth; Giacomo Cavaletto; Gianfranco Curletti; Sarah M. Devine; Joseph A. Francese; Emily K. L. Franzen; Filippo Giannone; Mischa Giasson; Jerzy M. Gutowski; Cory Hughes; et al. (Journal of Pest Science, 2025)
Semiochemical-baited traps are a key component of post-border surveillance for detection of non-native and potentially invasive bark and wood-boring beetles (Buprestidae, Cerambycidae, Curculionidae: Scolytinae) at risk of introduction in untreated woody materials used in global trade. Because the particular species that may arrive with imported goods is unknown, plant protection agencies need trapping protocols that effectively survey all three taxa. Baiting traps with host volatiles and aggregation/sex pheromones of longhorn beetles increases efficacy of detecting Cerambycidae and Scolytinae, but its effect on detection of Agrilus species and other jewel beetles is unknown. In this multi-country trapping study we found that the addition of ethanol and common aggregation/sex pheromones of longhorn beetles to green multi-funnel traps placed in the mid-upper forest canopy had negative effects on abundance of Agrilus species and other jewel beetles collected but no effect on their species richness, and significant positive effects on species richness and abundance of Cerambycidae and Scolytinae. Baiting green canopy traps with longhorn beetle pheromones increased the efficacy of traps for detecting total target taxa of bark and wood-boring beetles at risk of international movement in untreated woody materials. This information is beneficial for the design of multi-taxa surveys, potentially saving money and resources without decreasing trapping efficacy.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Data-driven mathematical modeling of sleep consolidation in early childhood - Christina Athanasouli; Shelby R. Stowe; Monique K. LeBourgeois; Victoria Booth; Cecilia G. Diniz Behn (Journal of Theoretical Biology, 2024)

Efficacy of trapping protocols for Agrilus jewel beetles: a multi-country assessment - Giacomo Santoiemma; David Williams; Everett G. Booth; Giacomo Cavaletto; James Connell; Gianfranco Curletti; Maarten de Groot; Sarah M. Devine; Abigail Enston; Joseph A. Francese; Emily K. L. Franzen; Mischa Giasson; et al. (Journal of Pest Science, 2024)
The genus Agrilus is one of the most diverse insect genera worldwide. The larval feeding activity causes extensive damage in both forests and orchards. In addition, more than 30 species have been introduced outside their native range so far, including the emerald ash borer Agrilus planipennis Fairmaire. Thus, the availability of efficient trapping protocols for early detection of Agrilus species at entry points is of utmost importance. In this study we tested whether trapping protocols developed for surveillance of A. planipennis in North America were also effective for other Agrilus species. In particular, through a multi-country assessment we compared the efficacy of detecting Agrilus species on: (i) green glue-coated prism traps vs. green Fluon-coated multi-funnel traps when baited with the green leaf volatile ( Z )-3-hexenol or left unbaited; and (ii) green multi-panel traps vs. green multi-panel traps baited with dead adult Agrilus beetles (decoys). A total of 23,481 individuals from 45 Agrilus species were caught. Trap design significantly affected both species richness and abundance of Agrilus species in several of the countries where the trapping experiments were carried out, and green prism traps outperformed green multi-funnel traps in most cases. On the contrary, the addition of a ( Z )-3-hexenol lure or dead adult beetle decoys on to traps did not improve trap catches. Our study highlights that reliable trap models to survey Agrilus species are already available, but also that there is the clear need to further investigate chemical ecology of Agrilus species to develop semiochemical lures that can improve detection efficacy.

Design and calibration of a nitrate decision support tool for groundwater wells in Wisconsin, USA - Paul F. Juckem; Nicholas T. Corson-Dosch; Laura A. Schachter; Christopher T. Green; Kelsie M. Ferin; Eric G. Booth; Christopher J. Kucharik; Brian P. Austin; Leon J. Kauffman (Environmental Modelling & Software, 2024)

Further insights into killer whales Orcinus orca preying on white sharks Carcharodon carcharias in South Africa - A Towner; P Micarelli; D Hurwitz; MJ Smale; AJ Booth; C Stopforth; E Jacobs; FR Reinero; V Ricci; A Di Bari; S Gavazzi; G Carugno; et al. (African Journal of Marine Science, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Generating environmental sampling and testing data for micro- and nanoplastics for use in life cycle impact assessment - Cecilia Askham; Valentina H. Pauna; Anne-Marie Boulay; Peter Fantke; Olivier Jolliet; Jérôme Lavoie; Andy M. Booth; Claire Coutris; Francesca Verones; Miriam Weber; Martina G. Vijver; Amy Lusher; et al. (Science of The Total Environment, 2023)

NREM–REM alternation complicates transitions from napping to non-napping behavior in a three-state model of sleep–wake regulation - Christina Athanasouli; Kelsey Kalmbach; Victoria Booth; Cecilia G. Diniz Behn (Mathematical Biosciences, 2023)

Foliar Nutrients Reflect Variation in Floristic Quality and Hydrology of Calcareous Fens - Arthur C. Ryzak; David Bart; Eric G. Booth; Steven P. Loheide (Wetlands, 2022)

Modeling population effects of the Deepwater Horizon oil spill on a long‐lived species - Lori H. Schwacke; Tiago A. Marques; Len Thomas; Cormac G. Booth; Brian C. Balmer; Ashley Barratclough; Kathleen Colegrove; Sylvain De Guise; Lance P. Garrison; Forrest M. Gomez; Jeanine S. Morey; Keith D. Mullin; et al. (Conservation Biology, 2022)
The 2010 Deepwater Horizon (DWH) oil spill exposed common bottlenose dolphins ( Tursiops truncatus ) in Barataria Bay, Louisiana to heavy oiling that caused increased mortality and chronic disease and impaired reproduction in surviving dolphins. We conducted photographic surveys and veterinary assessments in the decade following the spill. We assigned a prognostic score (good, fair, guarded, poor, or grave) for each dolphin to provide a single integrated indicator of overall health, and we examined temporal trends in prognostic scores. We used expert elicitation to quantify the implications of trends for the proportion of the dolphins that would recover within their lifetime. We integrated expert elicitation, along with other new information, in a population dynamics model to predict the effects of observed health trends on demography. We compared the resulting population trajectory with that predicted under baseline (no spill) conditions. Disease conditions persisted and have recently worsened in dolphins that were presumably exposed to DWH oil: 78% of those assessed in 2018 had a guarded, poor, or grave prognosis. Dolphins born after the spill were in better health. We estimated that the population declined by 45% (95% CI 14–74) relative to baseline and will take 35 years (95% CI 18–67) to recover to 95% of baseline numbers. The sum of annual differences between baseline and injured population sizes (i.e., the lost cetacean years) was 30,993 (95% CI 6607–94,148). The population is currently at a minimum point in its recovery trajectory and is vulnerable to emerging threats, including planned ecosystem restoration efforts that are likely to be detrimental to the dolphins’ survival. Our modeling framework demonstrates an approach for integrating different sources and types of data, highlights the utility of expert elicitation for indeterminable input parameters, and emphasizes the importance of considering and monitoring long‐term health of long‐lived species subject to environmental disasters. Article impact statement : Oil spills can have long‐term consequences for the health of long‐lived species; thus, effective restoration and monitoring are needed.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A pathogenic deletion in Forkhead Box L1 (FOXL1) identifies the first otosclerosis (OTSC) gene - Nelly Abdelfatah; Ahmed A. Mostafa; Curtis R. French; Lance P. Doucette; Cindy Penney; Matthew B. Lucas; Anne Griffin; Valerie Booth; Christopher Rowley; Jessica E. Besaw; Lisbeth Tranebjærg; Nanna Dahl Rendtorff; et al. (Human Genetics, 2022)
Otosclerosis is a bone disorder of the otic capsule and common form of late-onset hearing impairment. Considered a complex disease, little is known about its pathogenesis. Over the past 20 years, ten autosomal dominant loci ( OTSC1-10 ) have been mapped but no genes identified. Herein, we map a new OTSC locus to a 9.96 Mb region within the FOX gene cluster on 16q24.1 and identify a 15 bp coding deletion in Forkhead Box L1 co-segregating with otosclerosis in a Caucasian family. Pre-operative phenotype ranges from moderate to severe hearing loss to profound sensorineural loss requiring a cochlear implant. Mutant FOXL1 is both transcribed and translated and correctly locates to the cell nucleus. However, the deletion of 5 residues in the C-terminus of mutant FOXL1 causes a complete loss of transcriptional activity due to loss of secondary (alpha helix) structure. FOXL1 (rs764026385) was identified in a second unrelated case on a shared background. We conclude that FOXL1 (rs764026385) is pathogenic and causes autosomal dominant otosclerosis and propose a key inhibitory role for wildtype Foxl1 in bone remodelling in the otic capsule. New insights into the molecular pathology of otosclerosis from this study provide molecular targets for non-invasive therapeutic interventions.

Agricultural Landscape Transformation Needed to Meet Water Quality Goals in the Yahara River Watershed of Southern Wisconsin - Tracy A. Campbell; Eric G. Booth; Claudio Gratton; Randall D. Jackson; Christopher J. Kucharik (Ecosystems, 2022)

A comparative analysis of genetic hearing loss phenotypes in European/American and Japanese populations - W. Daniel Walls; Hideaki Moteki; Taylor R. Thomas; Shin-ya Nishio; Hidekane Yoshimura; Yoichiro Iwasa; Kathy L. Frees; Carla J. Nishimura; Hela Azaiez; Kevin T. Booth; Robert J. Marini; Diana L. Kolbe; et al. (Human Genetics, 2020)

Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - Dianne L. McLean; Miles J. G. Parsons; Andrew R. Gates; Mark C. Benfield; Todd Bond; David J. Booth; Michael Bunce; Ashley M. Fowler; Euan S. Harvey; Peter I. Macreadie; Charitha B. Pattiaratchi; Sally Rouse; et al. (Frontiers in Marine Science, 2020)

Methods for Monitoring for the Population Consequences of Disturbance in Marine Mammals: A Review - Cormac G. Booth; Rachael R. Sinclair; John Harwood (Frontiers in Marine Science, 2020)

Food for thought: Harbor porpoise foraging behavior and diet inform vulnerability to disturbance - Cormac G. Booth (Marine Mammal Science, 2020)
Research has shown that noise disturbance can disrupt the behavior of harbor porpoises. The significance of such disturbance is unclear. However, these animals may be vulnerable to starvation when disturbed due to their high energy requirements. Important parameters determining harbor porpoise energy balance are the size and energy content of prey, their foraging behavior and their energetic requirements for homeostasis, growth, and reproduction. Energy intake can be estimated using published data from tagged animals. Such analysis indicates a broad range of plausible levels of energy intake, in line with those from captive studies. Metabolizable energy intake estimates were most strongly affected by variations in target prey size and to a lesser extent, by the foraging intensity of porpoises. In all but the worst case scenarios, harbor porpoises are well equipped for their ecological niche due to their generalist diet, consisting of a range of moderate to high energy‐density prey combined with ultra‐high foraging rates and high capture success. If animals can find suitable prey, porpoises may be capable of recovering from some lost foraging opportunities. Minimizing disturbances is, however, important for their health. Further research into prey and the environment are required to fully test the assumption of vulnerability.

The Future of Midlatitude Cyclones - Jennifer L. Catto; Duncan Ackerley; James F. Booth; Adrian J. Champion; Brian A. Colle; Stephan Pfahl; Joaquim G. Pinto; Julian F. Quinting; Christian Seiler (Current Climate Change Reports, 2019)
Purpose of Review This review brings together recent research on the structure, characteristics, dynamics, and impacts of extratropical cyclones in the future. It draws on research using idealized models and complex climate simulations, to evaluate what is known and unknown about these future changes. Recent Findings There are interacting processes that contribute to the uncertainties in future extratropical cyclone changes, e.g., changes in the horizontal and vertical structure of the atmosphere and increasing moisture content due to rising temperatures. Summary While precipitation intensity will most likely increase, along with associated increased latent heating, it is unclear to what extent and for which particular climate conditions this will feedback to increase the intensity of the cyclones. Future research could focus on bridging the gap between idealized models and complex climate models, as well as better understanding of the regional impacts of future changes in extratropical cyclones.

Some Old Movies Become Classics – A Case Study Determining the Scientific Value of ROV Inspection Footage on a Platform on Australia’s North West Shelf - Paul G. Thomson; Ashley M. Fowler; Andrew R. Davis; Charitha B. Pattiaratchi; David J. Booth (Frontiers in Marine Science, 2018)

Extreme precipitation and phosphorus loads from two agricultural watersheds - Stephen R. Carpenter; Eric G. Booth; Christopher J. Kucharik (Limnology and Oceanography, 2018)
Phosphorus runoff from agricultural land is a major cause of eutrophication in lakes and reservoirs. Frequency and intensity of extreme precipitation events are increasing in agricultural regions of the Upper Midwestern U.S., and these increases are projected to continue as climate warms. We quantified the linkage between extreme daily precipitation and extreme daily discharge, phosphorus (P) load, and P concentration for Pheasant Branch and the Yahara River, two tributaries of Lake Mendota, Wisconsin, U.S.A. using the generalized Pareto distribution. Although precipitation extremes have increased since 1940, over the shorter period of stream monitoring (1994–2015 for Pheasant Branch and 1991–2015 for Yahara) there is no significant trend in extreme precipitation. Nonetheless a disproportionate number of extreme precipitation events (for example seven of the 11 largest 24‐h events since 1901) occurred during the period of stream monitoring. Daily precipitation extremes were associated with extremes in daily discharge and P load. P load return levels increased steeply and almost linearly with precipitation on log‐log axes. The trend toward more frequent and intense precipitation extremes will increase P loading and intensify the eutrophication of the lake, unless the excessive P enrichment of the watershed is reversed.

The Influence of Legacy P on Lake Water Quality in a Midwestern Agricultural Watershed - Melissa Motew; Xi Chen; Eric G. Booth; Stephen R. Carpenter; Pavel Pinkas; Samuel C. Zipper; Steven P. Loheide; Simon D. Donner; Kai Tsuruta; Peter A. Vadas; Christopher J. Kucharik (Ecosystems, 2017)

Time dependent pharmacokinetics of pembrolizumab in patients with solid tumor and its correlation with best overall response - Hongshan Li; Jingyu Yu; Chao Liu; Jiang Liu; Sriram Subramaniam; Hong Zhao; Gideon M. Blumenthal; David C. Turner; Claire Li; Malidi Ahamadi; Rik de Greef; Manash Chatterjee; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Widespread gene flow between oceans in a pelagic seabird species complex - Katherine A. Booth Jones; Malcolm A. C. Nicoll; Claire Raisin; Deborah A. Dawson; Helen Hipperson; Gavin J. Horsburgh; Jim J. Groombridge; Stefanie M. H. Ismar; Paul Sweet; Carl G. Jones; Vikash Tatayah; Kevin Ruhomaun; et al. (Molecular Ecology, 2017)
Global‐scale gene flow is an important concern in conservation biology as it has the potential to either increase or decrease genetic diversity in species and populations. Although many studies focus on the gene flow between different populations of a single species, the potential for gene flow and introgression between species is understudied, particularly in seabirds. The only well‐studied example of a mixed‐species, hybridizing population of petrels exists on Round Island, in the Indian Ocean. Previous research assumed that Round Island represents a point of secondary contact between Atlantic ( Pterodroma arminjoniana ) and Pacific species ( Pterodroma neglecta and Pterodroma heraldica ). This study uses microsatellite genotyping and tracking data to address the possibility of between‐species hybridization occurring outside the Indian Ocean. Dispersal and gene flow spanning three oceans were demonstrated between the species in this complex. Analysis of migration rates estimated using bayesass revealed unidirectional movement of petrels from the Atlantic and Pacific into the Indian Ocean. Conversely, structure analysis revealed gene flow between species of the Atlantic and Pacific oceans, with potential three‐way hybrids occurring outside the Indian Ocean. Additionally, geolocation tracking of Round Island petrels revealed two individuals travelling to the Atlantic and Pacific. These results suggest that interspecific hybrids in Pterodroma petrels are more common than was previously assumed. This study is the first of its kind to investigate gene flow between populations of closely related Procellariiform species on a global scale, demonstrating the need for consideration of widespread migration and hybridization in the conservation of threatened seabirds.

Response to “Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al” - Alexandra C. G. Thomson; Paul H. York; Tim M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2016)

Stress analysis of NW Jordan: New episode of tectonic rejuvenation related to the Dead Sea transform fault - M. Alawabdeh; J. V. Pérez-Peña; J. M. Azañón; G. Booth-Rea; A. M. Abed; M. Atallah; J. P. Galve (Arabian Journal of Geosciences, 2016)

Shifting drivers and static baselines in environmental governance: challenges for improving and proving water quality outcomes - Sean Gillon; Eric G. Booth; Adena R. Rissman (Regional Environmental Change, 2016)

Movement restriction does not modulate sensory and perceptual effects of exercise-induced arm pain - Markus Hübscher; Simon Tu; Tasha Stanton; G. Lorimer Moseley; Benedict M. Wand; John Booth; James H. McAuley (European Journal of Applied Physiology, 2015)

Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism - Alexandra C. G. Thomson; Paul H. York; Timothy M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2015)

Extreme daily loads: role in annual phosphorus input to a north temperate lake - Stephen R. Carpenter; Eric G. Booth; Christopher J. Kucharik; Richard C. Lathrop (Aquatic Sciences, 2015)

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

Changing forest water yields in response to climate warming: results from long‐term experimental watershed sites across North America - Irena F. Creed; Adam T. Spargo; Julia A. Jones; Jim M. Buttle; Mary B. Adams; Fred D. Beall; Eric G. Booth; John L. Campbell; Dave Clow; Kelly Elder; Mark B. Green; Nancy B. Grimm; et al. (Global Change Biology, 2014)
Climate warming is projected to affect forest water yields but the effects are expected to vary. We investigated how forest type and age affect water yield resilience to climate warming. To answer this question, we examined the variability in historical water yields at long‐term experimental catchments across Canada and the United States over 5‐year cool and warm periods. Using the theoretical framework of the Budyko curve, we calculated the effects of climate warming on the annual partitioning of precipitation ( P ) into evapotranspiration ( ET ) and water yield. Deviation ( d ) was defined as a catchment's change in actual ET divided by P [ AET / P ; evaporative index ( EI )] coincident with a shift from a cool to a warm period – a positive d indicates an upward shift in EI and smaller than expected water yields, and a negative d indicates a downward shift in EI and larger than expected water yields. Elasticity was defined as the ratio of interannual variation in potential ET divided by P ( PET / P ; dryness index) to interannual variation in the EI – high elasticity indicates low d despite large range in drying index (i.e., resilient water yields), low elasticity indicates high d despite small range in drying index (i.e., nonresilient water yields). Although the data needed to fully evaluate ecosystems based on these metrics are limited, we were able to identify some characteristics of response among forest types. Alpine sites showed the greatest sensitivity to climate warming with any warming leading to increased water yields. Conifer forests included catchments with lowest elasticity and stable to larger water yields. Deciduous forests included catchments with intermediate elasticity and stable to smaller water yields. Mixed coniferous/deciduous forests included catchments with highest elasticity and stable water yields. Forest type appeared to influence the resilience of catchment water yields to climate warming, with conifer and deciduous catchments more susceptible to climate warming than the more diverse mixed forest catchments.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

EEFIT mission to Haiti following the 12th January 2010 earthquake - S. P. G. Madabhushi; K. Saito; E. D. Booth (Bulletin of Earthquake Engineering, 2013)

The effect of incubation temperature on hatchling quality in the olive ridley turtle, Lepidochelys olivacea, from Alas Purwo National Park, East Java, Indonesia: implications for hatchery management - R. I. Maulany; D. T. Booth; G. S. Baxter (Marine Biology, 2012)

Influence of poultry meal, meat meal or soybean meal inclusion on weight gain and production characteristics of Australian snapper Pagrus auratus - M. A. Booth; G. L. Allan; A. J. Anderson (Aquaculture International, 2012)

Mycorrhizal networks counteract competitive effects of canopy trees on seedling survival - Michael G. Booth; Jason D. Hoeksema (Ecology, 2010)
The dynamics of forest ecosystems depend largely on the survival of seedlings in their understories, but seedling survival is known to be limited by preemption of light and soil resources by overstory trees. It has been hypothesized that “common mycorrhizal networks,” wherein roots of seedlings are linked to overstory trees by symbiotic mycorrhizal fungi, offset some or all of the negative effects of trees on seedlings. Here we report the results of an unambiguous experimental test of this hypothesis in a monodominant Pinus radiata forest. We also tested the hypothesis that adaptive differentiation among plant populations causes local plant genotypes to respond more positively to mycorrhizal networks than nonlocal plant genotypes. Our results demonstrate large positive effects of overstory mycorrhizal networks on seedling survival, along with simultaneous negative effects of tree roots, regardless of whether plant genotypes were locally derived. Physiological and leaf‐chemistry measurements suggest that seedlings connected to common mycorrhizal networks benefited from increased access to soil water. The similar magnitude of the positive and negative overstory effects on seedlings and the ubiquity of mycorrhizal networks in forests suggest that mycorrhizal networks fundamentally influence the demographic and community dynamics of forest trees.

Molecular phylogenetic biodiversity assessment of arctic and boreal ectomycorrhizal Lactarius Pers. (Russulales; Basidiomycota) in Alaska, based on soil and sporocarp DNA - JÓZSEF GEML; GARY A. LAURSEN; INA TIMLING; JACK M. MCFARLAND; MICHAEL G. BOOTH; NIALL LENNON; CHAD NUSBAUM; D. LEE TAYLOR (Molecular Ecology, 2009)
Despite the critical roles fungi play in the functioning of ecosystems, especially as symbionts of plants and recyclers of organic matter, their biodiversity is poorly known in high‐latitude regions. In this paper, we discuss the molecular diversity of one of the most diverse and abundant groups of ectomycorrhizal fungi: the genus Lactarius Pers. We analysed internal transcribed spacer rDNA sequences from both curated sporocarp collections and soil polymerase chain reaction clone libraries sampled in the arctic tundra and boreal forests of Alaska. Our genetic diversity assessment, based on various phylogenetic methods and operational taxonomic unit (OTU) delimitations, suggests that the genus Lactarius is diverse in Alaska, with at least 43 putative phylogroups, and 24 and 38 distinct OTUs based on 95% and 97% internal transcribed spacer sequence similarity, respectively. Some OTUs were identified to known species, while others were novel, previously unsequenced groups. Non‐asymptotic species accumulation curves, the disparity between observed and estimated richness, and the high number of singleton OTUs indicated that many Lactarius species remain to be found and identified in Alaska. Many Lactarius taxa show strong habitat preference to one of the three major vegetation types in the sampled regions (arctic tundra, black spruce forests, and mixed birch‐aspen‐white spruce forests), as supported by statistical tests of UniFrac distances and principal coordinates analyses (PCoA). Together, our data robustly demonstrate great diversity and nonrandom ecological partitioning in an important boreal ectomycorrhizal genus within a relatively small geographical region. The observed diversity of Lactarius was much higher in either type of boreal forest than in the arctic tundra, supporting the widely recognized pattern of decreasing species richness with increasing latitude.

Molecular determinants of ligand-directed signaling for the histamine H1 receptor - R. G. Booth; L. Fang; A. Wilczynski; S. Sivendren; Z. Sun; S. Travers; M. Bruysters; K. Sansuk; R. Leurs (Inflammation Research, 2008)

First detection and confirmation of spring viraemia of carp virus in common carp, Cyprinus carpio L., from Hamilton Harbour, Lake Ontario, Canada - K A Garver; A G Dwilow; J Richard; T F Booth; D R Beniac; B W Souter (Journal of Fish Diseases, 2007)
In June 2006, 150 wild common carp were sampled from Hamilton Harbour, Lake Ontario, Canada. Tissue pools consisting of kidney, spleen and encephalon were screened for viruses as a condition facilitating the export of live carp to France. Cytopathic effect (CPE), indicative of a viral infection, became evident after 8 days of incubation at 15 °C. Eighteen of 30 tissue pools (five fish per pool) eventually demonstrated viral CPE. The viral pathogen was initially cultured and isolated on the epithelioma papulosum cyprini cell line and subsequently shown to produce CPE in the fathead minnow and bluegill fin cell lines. Electron microscopy demonstrated the virus to be a rhabdovirus. Reverse transcriptase‐polymerase chain reaction assay and nucleotide sequence analysis identified the isolate as spring viraemia of carp virus (SVCV). Phylogenetic analysis of a 533 bp region of the glycoprotein gene grouped the Canadian isolate in SVCV genogroup Ia together with isolates from Asia and the USA. Sequence comparisons revealed the Hamilton Harbour, Lake Ontario isolate to be most similar to an isolate obtained from common carp in the Calumet Sag Channel in Illinois in 2003 (98.9% nucleotide identity). This is the first report of the detection of SVCV in Canada.

Measuring degradation of zinc phosphide residues in possum stomach contents - L. E. Brown; P. Fisher; G. Wright; L. Booth (Bulletin of Environmental Contamination and Toxicology, 2007)

Quantitative Bioanalytical Methods Validation and Implementation: Best Practices for Chromatographic and Ligand Binding Assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (Pharmaceutical Research, 2007)

Novel ligands stabilize stereo-selective conformations of the histamine H1 receptor to activate catecholamine synthesis - R. G. Booth; N. H. Moniri (Inflammation Research, 2007)

Workshop/conference report—Quantitative bioanalytical methods validation and implementation: Best practices for chromatographic and ligand binding assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (The AAPS Journal, 2007)

Frequency distributions of transient regional climate change from perturbed physics ensembles of general circulation model simulations - G. R. Harris; D. M. H. Sexton; B. B. B. Booth; M. Collins; J. M. Murphy; M. J. Webb (Climate Dynamics, 2006)

Alternative Dynamic Regimes and Trophic Control of Plant Succession - Oswald J. Schmitz; Elizabeth L. Kalies; Michael G. Booth (Ecosystems, 2006)

Gene expression and genotyping studies implicate the interleukin 7 receptor in the pathogenesis of primary progressive multiple sclerosis - D. R. Booth; A. T. Arthur; S. M. Teutsch; C. Bye; J. Rubio; P. J. Armati; J. D. Pollard; R. N. S. Heard; G. J. Stewart (Journal of Molecular Medicine, 2005)

Impact of pharmacometrics on drug approval and labeling decisions: A survey of 42 new drug applications - Venkatesh A. Bhattaram; Brian P. Booth; Roshni P. Ramchandani; B. Nhi Beasley; Yaning Wang; Veneeta Tandon; John Z. Duan; Raman K. Baweja; Patrick J. Marroum; Ramana S. Uppoor; Nam Atiqur Rahman; Chandrahas G. Sahajwalla; et al. (The AAPS Journal, 2005)

Ligand-directed multifunctional signaling of histamine H1 receptors - R. G. Booth; N. H. Moniri (Inflammation Research, 2005)

Mycorrhizal networks mediate overstorey‐understorey competition in a temperate forest - Michael G. Booth (Ecology Letters, 2004)
In forests, common mycorrhizal networks (CMNs) often connect the roots of neighbouring plants. Observations of material flows between hosts connected by CMNs have given rise to the hypothesis that CMNs limit the negative effects of competition by overstorey trees on seedlings recruiting underneath them. I conducted an experiment in a temperate forest dominated by ectomycorrhizal conifers and hardwoods to isolate the effects of CMNs on the growth and survival of four tree species that co‐occur in the understorey. Ectomycorrhizal networks had strong negative effects on the survival of an arbuscular mycorrhizal species, Acer rubrum , and neutral effects on the survival of three ectomycorrhizal species, Betula allegheniensis , Pinus strobus , and Tsuga canadensis . CMNs had positive effects on the growth of at least one ectomycorrhizal species, P. strobus . Interspecific differences in juvenile responses to CMNs may influence forest community development, promoting coexistence of some tree species while limiting the success of others.

Functional heterogeneity of histamine H 1 receptors - N. H. Moniri; R. G. Booth (Inflammation Research, 2004)

Small‐scale faulting, topographic steps and seismic ruptures in the Alhambra (Granada, southeast Spain - J. M. Azañón; A. Azor; G. Booth‐Rea; F. Torcal (Journal of Quaternary Science, 2004)
The Alhambra (14th century AD ) in Granada (southeast Spain) is built at the summit of a Pliocene to Lower Pleistocene conglomeratic formation. Tens of small‐scale normal faults crop out along the northern hillslope of the Alhambra, which have a N130–N150°E strike, dipping 65–75° mostly to the southwest. These are closely spaced faults (approximately 5–30 m) with centimetre to several metre displacements. Several topographic steps in this area coincide with hectometre‐ to kilometre‐scale faults with the same kinematics as the small‐scale ones. Some of these faults appear to be active and related to the present seismicity detected in this region, and associated with the cracks and other damage observed in the Alhambra. Several focal mechanisms calculated in this study are in accordance with the dominant NW–SE orientated normal faults. We interpret that the topographic steps of these faults are a consequence of repeated earthquakes during the past 800 ka. The last large earthquake of approximately 5.1 magnitude in this area occurred in 1431, destroying the Alixares Palace, the Arabian fence and part of the Alhambra wall. We consider the seismic risk associated with these faults to be moderate, as the displacement is partitioned into several hectometre‐ to kilometre‐scale faults. Copyright © 2004 John Wiley & Sons, Ltd.

Estuarine Macrobenthic Community Structure in the Hawkesbury River, Australia: Relationships with Sediment Physicochemical and Anthropogenic Parameters - G. R. MacFarlane; D. J. Booth (Environmental Monitoring and Assessment, 2001)

Monitoring Urban Streams: Strategies and Protocols for Humid-Region Lowland Systems - Jenna G. Scholz; Derek B. Booth (Environmental Monitoring and Assessment, 2001)

Degradation of Sodium Monofluoroacetate (1080) and Fluorocitrate in Water - L. H. Booth; S. C. Ogilvie; G. R. Wright; C. T. Eason (Bulletin of Environmental Contamination and Toxicology, 1999)

Methylglyoxal production in bacteria: suicide or survival? - G. P. Ferguson; S. Tötemeyer; M. J. MacLean; I. R. Booth (Archives of Microbiology, 1998)

Remote monitoring of heart rate as a measure of recovery in angled Atlantic salmon, Salmo salar (L.) - W. G. Anderson; R. Booth; T. A. Beddow; R. S. McKinley; B. Finstad; F. Økland; D. Scruton (Hydrobiologia, 1998)

Introgression of quantitative trait loci (QTLs) determining stripe rust resistance in barley: an example of marker-assisted line development - T. Toojinda; E. Baird; A. Booth; L. Broers; P. Hayes; W. Powell; W. Thomas; H. Vivar; G. Young (Theoretical and Applied Genetics, 1998)

Molecular and biological characterization of new strains of murine cytomegalovirus isolated from wild mice - T. W. M. Booth; A. A. Scalzo; C. Carrello; P. A. Lyons; Helen E. Farrell; G. R. Singleton; G. R. Shellam (Archives of Virology, 1993)